Effects of packaging methods combined with frozen temperature on the color of frozen beef rolls. (January 2021) - Wang, Fangfang; Liang, Rongrong; Zhang, Yimin; Gao, Shujuan; Zhu, Lixian; Niu, Lebao; Luo, Xin; Mao, Yanwei; Hopkins, David L.
Abstract: Beef rolls for hot pot are usually stored and transported in a frozen state, and the beef color deteriorates quickly. This paper reports on an investigation into the effect of packaging method, freezing temperature and storage time on instrumental color, pH, myoglobin state, lipid oxidation (TBARS) and total volatile basic nitrogen (TVB-N) of beef rolls. It was shown that the color of beef rolls at −18 °C was better than that at −12 °C overall, and the OxyMb% and pH values were higher, while the MetMb% and TBARS were lower with storage at −18 °C. With the extension of storage time, the instrumental color, OxyMb% and pH values of beef rolls decreased. Correspondingly, the MetMb% and TBARS showed an upward trend. However, the TVB-N of all treatments did not exceed the Chinese standard during 180d of storage. The results of this paper provide a number of recommendations for the storage of frozen beef rolls to extend color-shelf life.